Impact of Obesity in Children with Narcolepsy. (10th April 2013) - Inocente, Clara Odilia; Lavault, Sophie; Lecendreux, Michel; Dauvilliers, Yves; Reimao, Rubens; Gustin, Marie‐Paule; Castets, Sarah; Spiegel, Karine; Lin, Jian‐Sheng; Arnulf, Isabelle; Franco, Patricia
Summary Aims To evaluate the impact of obesity on clinical and sleep characteristics in a population of narcoleptic children. Methods Data from the children diagnosed with idiopathic narcolepsy in the National Reference Centers for Narcolepsy were collected between 2008 and 2011. Clinical and electrophysiological characteristics were compared between obese (body mass index [BMI] greater than P97) and nonobese children. Results The 117 children (65 boys, 59 de novo patients) had a mean age of 11.6 ± 3.1 years on diagnosis. Cataplexy was present in 81%, DQB1*0602 in 91%. Mean BMI was 23.2 ± 5.2 kg/m2 and BMI z‐score was 2.9 ± 2.6. Obesity was found in 60% with a similar prevalence in treated versus de novo patients and in patients with and without cataplexy. Sleepiness and cataplexy started earlier in obese children. Obese narcoleptic children had lower sleep efficiency, higher apnea hypopnea index and respiratory arousals index (RAI) than nonobese children. BMI z‐score was positively correlated with RAI. Obese children were more tired and missed more often school than nonobese children. Conclusion Obesity affects more than 50% of narcoleptic children, mostly younger at disease onset, and has a deleterious impact on sleep quality as well as on school attendance.